Hubungan Hafalan Al-Qur’an Terhadap Prestasi Belajar Bahasa Arab Siswa - Febri Kurniawan; Kasmudi; Heriansyah (Al Mitsali, 2022)
The background of this research needs to research the correlation of memorizing Al-Qur'an with learning achievement in Arabic. The researcher takes the formulation of this problem, namely is there a relationship between memorization of the Qur'an and achievement in Arabic?. This study aims to determine how strong the correlation between memorizing the Qur'an and learning achievement in Arabic and how significant is the relationship between memorizing the Qur'an and learning achievement in Arabic. The results of this study are expected to be an input for the development of science as well as information. which is useful. This study uses quantitative research, this research design uses a correlation design. This research was conducted at SMP Qur'an Darul Ikhlas Pringsewu. The sample of this study was 23 students from class VIII who were determined using non-probability sampling techniques with saturated sampling technique sampling. The data analysis technique uses the Product Moment correlation analysis technique. From the research results obtained a correlation coefficient value of 0.46 which is interpreted in the interpretation table that the value is in the interval 0.40 - 0.70 with the criteria between X and Y variables there is a moderate or sufficient correlation. It is known that the value of df = 21 with a significance level of 5% is obtained a value of 0.433. So it can be concluded that the "r" count is greater than the "r" table, at a significance level of 5% (0.46> 0433). Thus the null hypothesis (H_0) is rejected, while the alternative hypothesis (H_a) is accepted. The results of this study are expected to contribute to the knowledge of teachers, students and other researchers that the level of memorization of the Qur'an can affect learning achievement in Arabic.